2017
DOI: 10.1002/marc.201700179
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Tubular Aromatic Amide Helices

Abstract: Conjugated polymers may be induced by intra- and/or intermolecular non-covalent forces to fold into helical conformations. Helices formed by aromatic amide, hydrazide, and urea polymers possess a well-organized cavity and depth, which is defined by their degree of polymerization. Driving forces may be intramolecular hydrogen bonding and/or solvophobicity, or guest induction. The resulting long helices represent a new class of unimacromolecular dynamic tubular architectures that exhibit unique properties or fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 109 publications
0
19
0
1
Order By: Relevance
“…Early attempts to prepare fully hydrogen‐bonded polymeric aromatic foldamers often used the acyl chloride coupling method . Following this method to test a few polymerization conditions for coupling A and B , we found that 6.7 kDa (about 3.9 helical turns and 1.3 nm in helical height) is about the highest molecular weight we can obtain (entry 18 of Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early attempts to prepare fully hydrogen‐bonded polymeric aromatic foldamers often used the acyl chloride coupling method . Following this method to test a few polymerization conditions for coupling A and B , we found that 6.7 kDa (about 3.9 helical turns and 1.3 nm in helical height) is about the highest molecular weight we can obtain (entry 18 of Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Achieving this goal through polymerization has proven to be a challenging task, and can mostly be ascribed to the low reactivity of amines and carboxylic acids, which are destined to form covalent bonds but are highly rigidified by intramolecular hydrogen bonds. In fact, despite availability of diverse types of fully hydrogen‐bonded aromatic foldamers reported since the pioneering reports, the hitherto reported longest nanotube with a fully hydrogen‐bonded aromatic tubular cavity carries an average of 30 repeating units and a helical height of 1.4 nm, while partially hydrogen‐bonded polymers with a more flexible backbone could reach 6.1 nm …”
Section: Introductionmentioning
confidence: 99%
“…Presumably, this arises from the rigidity‐induced low reactivities of the reactive groups confined within the H‐bond‐rigidified backbone. In fact, the one‐pot polymerization method has not been very successful to date, and has only given rise to fully H‐bonded foldamer channels of ≤1.7 nm …”
Section: Figurementioning
confidence: 99%
“…Nevertheless, despite considerable contributions from the group of Huc et al., functional investigations on these aromatic foldamers have been limited to short oligomers of <1 nm in helical height because the multistep iterative preparation of foldamers with a long covalent helical backbone is synthetically challenging. If longer tubular foldamers can be efficiently prepared from their constituent repeating units by such as one‐pot polymerization, the corresponding functions can be expanded. As far as aromatic foldamers are concerned, one‐pot polymerization has thus far yielded long helical channels of >2 nm for only four types of aromatic foldamers stabilized by either electrostatic repulsions or solvophobic forces …”
Section: Figurementioning
confidence: 99%